Making Sense of Public Policy on Refugee Integration. Issue 1 (July 2020) - Ferris, Elizabeth
While immigrant integration is increasingly important for policy-makers, governments of countries approach the challenge of integration differently. In this article, I frame the issue of migrant/refugee integration in the larger context of political debates and policies about the entry of refugees and migrants. I then go on to analytic comparison of refugee integration policies in eleven developed countries, focusing on the interrelated domains of citizenship, language acquisition, and employment. These three domains are interrelated: acquiring language skills facilitates employment and (for most countries) is required for citizenship. I find considerable variation across these countries, which reflects their different historical contexts, but also the different policy choices that have been made in the countries. Even within the European Union, there is considerable variation between Member States in the emphasis they place, for example, on employment of refugees. While the study focuses primarily on policies developed at the national level, I conclude by stressing the importance of local initiatives to support refugee integration.